Cognitive-Pragmatic Aspects of Gender Linguistics - Musaeva Elena Kazimovna (Zien Journals, 2022)
The article deals with the issue of gender linguistics. Gender is studied as a social gender that determines the behavior of an individual in society, and how this behavior is perceived.
Keywords: Gender; gender identity; psychological gender; masculine